Fides quaerens intellectum: Un desafío siempre contemporáneo = Fides quaerens intellectum : An Ongoing Contemporary Challenge - Rouco, Mons Alfonso Carrasco (Isidorianum, 2022)
The essay extracts from a lecture on the contemporary challenges of theology, in the context of the magisterium of Pope Francis. The author discusses the theological task of always expanding the knowledge of the Gospel as part of God’s command to its People; starting from the first great inculturation in Greco-Roman societies, he shows this link between theology and the journey of the People of God. The author then highlights some of the new demands that theology must face to sustain this identification and fulfil its mission: to avoid the rationalist temptation to reinterpret God’s intervention in history; to widen the limits of a reason reduced to its mere empirical-mathematical components; and to respond to the hermeneutical challenge of re-enacting the relevance of the gospel to the contemporary People of God. It concludes by identifying some of these coordinates in the teachings of Francis’ Veritatis Gaudium.